Coherent Control of Perfect Optical Vortex Through Four-Wave Mixing in an Asymmetric Semiconductor Double Quantum Well - Deng, Xu; Shui, Tao; Yang, Wen-Xing (Frontiers in Physics, 2022)
A scheme for the coherent control of perfect optical vortex (POV) in an asymmetric double quantum well is proposed by exploiting the tunneling-induced highly efficient FWM. The OAM is completely transferred from a unique POV mode to the generated FWM field. Using experimentally achievable parameters, we identify the conditions under which resonant tunneling allows us to improve the quality of the vortex FWM field and engineer helical phase wavefront beyond what is achievable in the absence of resonant tunneling. Furthermore, we find that the intensity and phase patterns of the vortex FWM field are sensitive to the detuning of the probe field, but rather robust against the detuning of the coupling field. Subsequently, we perform the coaxial interference between the vortex FWM field and a same-frequency POV beam and show interesting interference properties, which allows us to measure TC of the output POV beam. Our result may find potential applications in quantum technologies based on POV in solids.